2020
DOI: 10.1111/sjop.12681
|View full text |Cite
|
Sign up to set email alerts
|

Externalizing behaviors and attachment disorganization in children of different‐sex separated parents: The protective role of joint physical custody

Abstract: The aim of this study was to examine the relationship between externalizing behaviors and the quality of attachment representations in preschool children, and to determine if family type and custody arrangement had a moderating effect on this relationship. The participants were 33 girls and 31 boys (n = 64) aged between three and six years (M = 4.75; SD = 0.87 years) and their mothers. Among them, 36 came from “intact” families, 13 were living mainly with their mothers and 15 were in joint physical custody. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(65 reference statements)
0
3
0
1
Order By: Relevance
“…Research in additional contexts is consequently needed. Yet, with the increase in the time and range of father involvement in childrearing world-wide, studies have pointed to the beneficial and distinct effects of the father on the child's neurobiological maturation (Feldman et al, 2019), and on the development of social competencies, particularly the child's capacity to manage aggression (Bacro & Macario de Medeiros, 2020;Feldman et al, 2013). Thus, depriving children opportunities for relationships with their fathers is generally not in their best interest.…”
Section: Multiple Attachment Relationships and Custody Decisions It mentioning
confidence: 99%
“…Research in additional contexts is consequently needed. Yet, with the increase in the time and range of father involvement in childrearing world-wide, studies have pointed to the beneficial and distinct effects of the father on the child's neurobiological maturation (Feldman et al, 2019), and on the development of social competencies, particularly the child's capacity to manage aggression (Bacro & Macario de Medeiros, 2020;Feldman et al, 2013). Thus, depriving children opportunities for relationships with their fathers is generally not in their best interest.…”
Section: Multiple Attachment Relationships and Custody Decisions It mentioning
confidence: 99%
“…Interestingly, although only a small number of studies which included exclusively young children (0-7 years), all studies except one [64] showed that children in nuclear families and SPC families had equal outcomes [12,50,51,60,63]. In contrast, children in LPC families had the worst outcomes in four of the six (60.0%) studies.…”
Section: Plos Onementioning
confidence: 96%
“…Several studies have tried to distil factors that may explain the differences in children's outcomes across living arrangements. Some of these factors include: socioeconomic status [4,[7][8][9], interparental conflict [10,11], parenting and parental factors [11], and parent-child relationship factors [12][13][14]. Prior research has also shown that in forerunner countries where SPC was legally implemented early on either as the preferred arrangement, such as in many Nordic countries and some parts of North America [15], the prevalence of SPC tends to be higher and be less strongly associated with parents' socio-economic status (SES) or conflict between them [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…È necessario, di conseguenza, svolgere ricerche anche in contesti diversi. Eppure, con il generale aumento in termini di tempo e di coinvolgimento paterno nella cura dei figli, gli studi hanno indicato molteplici effetti benefici della figura paterna sulla maturazione neurobiologica infantile (Feldman et al, 2019) e sullo sviluppo di competenze sociali, in particolare sulla capacità di gestire l'aggressività (Bacro & Macario de Medeiros, 2020;Feldman et al, 2013). Privare, dunque, i bambini dell'opportunità di relazionarsi ai loro padri non corrisponde, di norma, al loro superiore interesse; infatti, anche nelle famiglie tradizionali dove il coinvolgimento paterno è medio-basso, gli studi a lungo termine hanno mostrato gli effetti positivi della sensibilità paterna sullo sviluppo (Grossmann et al, 2008).…”
Section: Fraintendimenti Riguardo Alle Interazioni Fra Attaccamenti M...unclassified